Responses to Telomere Erosion in Plants - Amiard, Simon (Public Library of Science, 2014)
In striking contrast to animals, plants are able to develop and reproduce in the presence of significant levels of genome damage. This is seen clearly in both the viability of plants carrying knockouts for key recombination and DNA repair genes, which are lethal in vertebrates, and in the impact of telomere dysfunction. Telomerase knockout mice show accelerated ageing and severe developmental phenotypes, with effects on both highly proliferative and on more quiescent tissues, while cell death in Arabidopsis tert mutants is mostly restricted to actively dividing meristematic cells. Through phenotypic and whole-transcriptome RNAseq studies, we present here an analysis of the response of Arabidopsis plants to the continued presence of telomere damage. Comparison of second-generation and seventh-generation tert mutant plants has permitted separation of the effects of the absence of the telomerase enzyme and the ensuing chromosome damage. In addition to identifying a large number of genes affected by telomere damage, many of which are of unknown function, the striking conclusion of this study is the clear difference observed at both cellular and transcriptome levels between the ways in which mammals and plants respond to chronic telomeric damage.